Toxicity determination of crabs in Barangay Cagsao, Calabanga, Camarines Sur. - Gabay, Imee C. 4 0 16; 5 (2005)
ABSTRACT: The study focused on Toxicity Determination of crabs in Barangay Cagsao, Calabanga, Camirines Sur. The species collected were Doclea canalifera, Ocypode ceratophthalma, Actaeodes tomentosus, Metopopgrapsus messor, Leptodius exaratus, Ozius rugulosus, Thalamita crenata. Using A.O.A.C mouse bioassay toxicity level of eight species of crabs were determined. The whole crab was homogenized, weighted and added with a proportionate volume of 0.1 N HCI. After the process, the sample was boiled for few minutes and filtered by using cheesecloth. The acidic extract was inoculated intraperitoneally to mice and the time of injection and death was recorded, also behavior of the mice were observed. The result were both Actaeodes tomentosus and Pilumnus vespertilio exhibit high level of toxicity whereas, Ocypode ceratophthalma was said to be non-toxic. The rest considered low toxic level including Leptodius exaratus, O. rugulosus, T. cremata, Doclea canalifera, and M. messor. Signs and symptoms were also observed in mice including rapid breathing, wobbling gait, paralysis of hind limbs then death. It was found that the toxicity levels of various species of crabs are significantly different and that the mean mean levels are not all the same.
Thesis:(B.S. Biology)- Pamantasan ng Lungsod ng Maynila, 2005.
Keywords: 2 -- 0; 6; 20; 20; 2